A method for measuring the amplitude and phase of ultrashort laser pulses using self-modulation in a Kerr medium and spectral interferometry. (April 2017) - Andrianov, A.V.; Kim, A.V.; Khazanov, E.A.
Abstract: A new method is proposed for measuring the field of ultrashort pulses by assessing spectral interference between an input pulse and the pulse transmitted through a Kerr medium. The proposed iterative algorithm allows the pulse amplitude and phase to be reconstructed. Our numerical experiments demonstrate that the proposed algorithm can be used to reconstruct pulses with complex intensity and phase shapes and is stable to a noise in input data. The method requires that only one nonlinear element be placed in the laser beam to be studied.